The role of acoustic cues in time-to-passage judgments: judging time-to-passage of looming sounds - Silva, Rosa Mariana Macedo Tinoco da (2013)
8º Encontro Nacional da Associação Portuguesa de Psicologia Experimental : posters : títulos e resumos